Kajian Filosofis tentang Hukum dan Keadilan dari Pemikiran Klasik Sampai Pemikiran Modern - Bahder Johan Nasution (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
ABSTRACT Justice, since the first issue, has been the subject of study both among philosophers and among theologians, politicians and thinkers or legal experts. However, if there are questions about justice, could not be determined what measures are used to determine something is fair or not. Various answers about justice usually never or rarely satisfying so that continues to be debated, so it can be concluded that the various formulations of justice is a relative statement. This issue ultimately encourages many people to take a shortcut by submitting formulation of justice to the legislators and judges who will formulate it based on their own considerations.